Sintese de catalisadores pelo método Pechini utilizando glicerol como agente quelante para a decomposição catalítica do metano - Tenório, Nereu Victor Nazário (2018)
The Pechini method is a methodology of catalyst synthesis that uses citric acid to form chelates with metal ions, which undergo polyesterification when heated with ethylene glycol. It is a method studied since 1967, and comes, like any other method, undergoing variations and optimizations over the years. In the literature, published public publications involving the improvement of the methodology. Among the variables that are analyzed, we can mention variations in the proportion of citric acid: ethylene glycol and citric acid: aluminum, besides the thermal treatments, substitution of the complexing agent, among others. However, there are very few papers reporting a substitution of the chelating agent, ethylene glycol. Thus, this work systematically investigates the use of glycerol as polymerizing agent in substitution of the traditional ethylene glycol in the Pechini method to obtain alumina, followed by alumina impregnation with Fe, Ni or Co and consequent use in the Chemical Vapor Deposition reaction (CVD). It was obtained aluminas with area of up to 160 m2/g and through infrared spectroscopy the methodology was confirmed. After the impregnation of the metals in the alumina, the catalysts led up to 30% methane conversion.